A Preliminary Cadaveric MRI Study of Fetal Hip Development - Liu, Zhenqing; Li, Huixian; Wang, Shuai; Wu, Qianqian; Liu, Hongsheng (Frontiers in Surgery, 2022)
Purpose The earlier the detection of the hip joint is discovered, the better the final result. The purpose of this study aimed to investigate the fetal hip development using magnetic resonance imaging (MRI), so as to alert clinicians to possible abnormal development during intrauterine life. Method Measurements of 34 cadaver fetuses (68 hips) were obtained regarding acetabular width and depth, anterior bony acetabular index (ABAI), anterior cartilaginous acetabular index (ACAI), posterior bony acetabular index (PBAI), and posterior cartilaginous acetabular index (PCAI). The standard values of each acetabular measurement index were obtained, and the gestational age-measurement index change trend chart was drawn to comprehensively analyze the normal development law of the fetal hip joint. Results With the development of fetuses, the width and depth of acetabular increase linearly, and the slope of acetabular width was larger than that of depth. In addition, two change points during the 24th and 34th weeks of gestation were detected with regard to width. ABAI and PBAI also decreased. ABAI demonstrated an approximately linear trend, while PBAI shows a non-linear trend. During the 36th week, the change point in PBAI was observed. ACAI and PCAI exhibited slow increases, indicating a non-linear trend. During the 21st and 36th weeks of gestation, the change points regarding ACAI were observed. During the 22nd week of gestation, the change point for PCAI was observed. Conclusion Plots of the parameters obtained via MRI examinations of cadaver fetuses across gestational age comprehensively illustrated the fetal hip development. This developmental information about the hip joint has the potential to guide clinicians in the early detection of abnormal hip joint development during intrauterine life.